Blockchain architecture adoption in supply chain management : a dematel-based analysis of enablers - Jankin, Abdul Rahman (2024)
Blockchain technology has emerged as a pivotal innovation poised to transform Supply Chain Management. This study meticulously investigates the enablers facilitating the adoption of blockchain architecture within Malaysian SCM, addressing critical challenges such as high implementation costs, technical complexities, and organizational barriers. Utilizing an integrative multi-theoretic framework that combines the Technology-Organization-Environment (TOE) Framework and Diffusion of Innovations (DOI) Theory, the research employs the Decision-Making Trial and Evaluation Laboratory (DEMATEL) methodology to uncover the intricate interdependencies among identified enablers. Data were rigorously collected through purposive sampling of 25 SCM professionals and blockchain experts, ensuring the acquisition of rich, contextual insights. The findings underscore the paramount importance of technical competencies and robust IT infrastructure as foundational enablers for blockchain adoption. Technical literacy emerged as both a primary driver and a critical determinant, highlighting the necessity for continuous education and specialized training programs. Additionally, financial resources and system compatibility were identified as vital factors, emphasizing the need for strategic resource allocation and technological coherence to ensure seamless integration. Organizational flexibility and a culture of adaptability were found to be essential in fostering an environment conducive to blockchain adoption, while interoperability and compatibility further enhanced operational efficiency and transparency. This research makes significant contributions by providing empirically validated insights and a comprehensive analytical framework that offers actionable recommendations for industry practitioners and policymakers. By aligning with Malaysia’s National Blockchain Roadmap 2021-2025, the study not only advances academic discourse but also delivers practical guidance for enhancing transparency, efficiency, and security within supply chains. The methodological rigor and theoretical integration presented herein set a benchmark for future research, facilitating the ongoing digital transformation of SCM on a global scale. Ultimately, this study bridges the gap between theoretical constructs and practical applications, empowering organizations to harness the transformative potential of blockchain technology to achieve sustainable competitive advantage and operational excellence.